Effect of drought stress on the anatomical structure of red flowering Hoya coronaria Blume leaves - Rahmasari, Rahmasari; Henri, Henri; Robika, Robika (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2023)
.